DEVELOPMENT AND VALIDATION OF STABILITY INDICATING RP-HPLC METHOD FOR THE SIMULTANEOUS ESTIMATION OF ETHINYL ESTRADIOL AND GESTODENE IN BULK AND PHARMACEUTICAL DOSAGE FORMS - SUCHITRA, D.; SATYANARAYANA, BATTU (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Objective: The principal objective of this study is to develop and validate a simple, new, fast, selective, precise, and economic stability-indicating the RP-HPLC method for the simultaneous estimation of Ethinyl estradiol and Gestodene in a bulk and pharmaceutical dosage form. Methods: The present method was developed and validated on a Waters HPLC system using Phenomenex Gemini C18(250 mm × 4.6 mm i.d., 5 µm particle size) column and mobile phase composition of phosphate buffer: Acetonitrile (75:25 v/v) and the pH was adjusted to 3.6 using dilute orthophosphoric acid. The system was regulated at 1.0 ml/min flow rate at 237 nm UV detection. Results: The two drugs Ethinyl Estradiol and Gestodene, were eluted at 1.788 min and 3.475 min retention time, respectively. The analytical parameters such as accuracy, precision, linearity, LOD, LOQ, ruggedness, and robustness were used for validating the developed method according to International Conference on Harmonisation [ICH] guidelines. Linearity was exhibited over the concentration range of 10-50µg/ml and 25-125µg/ml for Ethinyl Estradiol and Gestodene, respectively. The method revealed the Limit of Detection and Quantitation values for Ethinyl Estradiol and Gestodene were 1.399µg/ml, 3.909µg/ml and 4.24µg/ml, 11.85µg/ml, respectively. The stress testing was carried out to give rise to degradation products by exposing the drugs to acid, alkali, thermal, oxidative, photolytic, and hydrolytic degradation. The obtained data showed that the content of Active pharmaceutical ingredients and the degradation products were successfully separated without any interference, which confirmed the stability-indicating nature of the developed method. Conclusion: The new, simple, rapid, selective, precise, and economic stability-indicating RP-HPLC method has been successfully developed and validated. It can be satisfactorily applied for the periodic laboratory quantitative estimation of Ethinyl Estradiol and Gestodene in formulations and active pharmaceutical ingredients.